How streamification challenges the Royal Danish Library’s collection of cultural heritage - Ægidius, Andreas Lenander (MedieKultur: Journal of media and communication research, 2021)
Danish legal deposit legislation mandates that the Royal Danish Library must collect contemporary culture for the benefi t of the public and researchers, now and in the future. In this article, I analyse how the move toward access models and the subsequent streamifi cation of media content challenges the collection of cultural heritage. I draw on empirical data from two central activities. The main empirical data stems from archival research and interviews with the library’s internal and external stakeholders. Th e second source of empirical data is the in-house testing performed by web curators when they analysed the collection of streaming-only content via an API from the Danish Broadcasting Corporation (DR). The analysis is followed by a discussion of the eff ects of streaming software and services on collection methods such as stream-ripping, screen capture (image or video), and research collaborations with the producers and distributors of born-digital content.